ROLES AND CHALLENGES OF PESANTREN INTELLECTUAL NETWORKS - Suwendi, Suwendi; Gama, Cipta Bakti; Farabi, Muhammad Fawwaz Farhan; Fuady, Farkhan; Arman, Arman (Universitas Islam Negeri Ar-Raniry, 2024)
Islamic boarding schools, known as pesantrens, serve as institutions dedicated to the preservation of knowledge passed down by their respective kiyai. The significance of pesantrens in Indonesia within the national education framework has expanded, influencing various sectors. Their impact on both national and international education has increased progressively, emphasizing modernization, educational quality, community dynamics within Islamic boarding schools, and human capital. The primary objective of this research is to elucidate the role played by the intellectual network of pesantrens in Indonesia. This investigation is conducted through a comprehensive review of existing literature using qualitative research methods. The analytical approach employed encompasses both descriptive and critical analyses. The study reveals that present-day pesantrens encounter a multitude of challenges that necessitate appropriate solutions. Among these challenges is the emergence of the Islamic reform movement. The enduring presence of pesantrens in Indonesia can be attributed to deep-rooted socio-historical foundations and the robust support of the intellectual network within these institutions. Consequently, these schools continue to fulfill a crucial function in disseminating knowledge within the community. It is evident from this study that the intellectual network of pesantrens plays a pivotal role in shaping societal dynamics. Moreover, this network must be attuned to contemporary challenges in order to ensure the sustained relevance and enhanced quality of pesantrens as key sources of scholarly expertise.